2020
DOI: 10.1109/tcpmt.2020.3026583
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Metallization Stacks Serve as Reliable Conductors on Ceramic-Based Substrates for Active Implants

Abstract: Hermetic and non-hermetic packages of active implantable medical devices are often fabricated of ceramics like alumina. Screen printed PtAu paste is the state of the art metallization for functional structures. Due to solid state and liquid diffusion of Au at thermal exposure, solder times are limited; otherwise metal structures tend to delaminate. Moreover, it was shown that PtAu with solder fails after 37.4 years. We established a thin film metallization on alumina process to overcome these disadvantages. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…The fracture is partly cohesive and partly adhesive in nature and shows extended scattering from 2 MPa up to the detection limit of 88 MPa. Unlike the previous studies [ 14 , 19 ], partial adhesive failure of the metal-ceramic interface was observed here, which may explain the lower adhesion and large variance. One difference was the larger surface roughness, which is decisive for the wettability during sputter deposition as well as the soldering process [ 36 ].…”
Section: Resultscontrasting
confidence: 96%
See 4 more Smart Citations
“…The fracture is partly cohesive and partly adhesive in nature and shows extended scattering from 2 MPa up to the detection limit of 88 MPa. Unlike the previous studies [ 14 , 19 ], partial adhesive failure of the metal-ceramic interface was observed here, which may explain the lower adhesion and large variance. One difference was the larger surface roughness, which is decisive for the wettability during sputter deposition as well as the soldering process [ 36 ].…”
Section: Resultscontrasting
confidence: 96%
“…The mean ultimate tensile strength needed to de-attach the wires was 31.1 MPa ( n = 47). Also, the median strength (20.1 MPa, n = 47) was higher than the conservative threshold of 17 MPa, set by a comparable study showing also a 32 MPa mean adhesion strength on commercial alumina [ 19 ]. No clear difference in maximum pull force between the copper rods soldered on the two different pad geometries was found.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations